Nonhydrogenic Effects in the Deceleration of Rydberg Atoms in Inhomogeneous Electric Fields - Vliegen, E; Wörner, H; Softley, T; Merkt, F (2004)
The effect of deviation from hydrogenic behavior on the deceleration of Rydberg atoms in inhomogeneous electric fields was analyzed. A particle which was nonpolar in the ground state was electrostatically decelerated. The effect was smaller by a factor of 2 because of adiabatic traversals of avoided crossings. The results show that the measurement of the decay of the Rydberg states at n = 25 sets a limit of ∼ μs to the time available for deceleration.